Liver Injury and Severe Covid 19 Associated without Prior Liver Disease - Naeem Ahmad, Sheikh Ali Ahmad Ajmal, Muhammad Tasneem Nawaz, Saud Javed Sara Khan, Ahmed Nawaz Banu, Imtiaz Nazam, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The aim of current study is to determine the association in liver injury in patients without preexisting liver disease by severe pandemic disease coronavirus. Study Design: Observational study Place and duration: THQ Hospital Kamalia. April 2020-March 2021 Methods: There were one hundred and three patients had corona virus illness were presented in this study. After obtaining informed written permission, the demographics of enrolled patients, including age, sex, and BMI, were recorded. Comorbidities signs and symptoms of disease were also recorded. Severity of disease and its adverse outcomes on liver were assessed in regular follow up. SPSS 21.0 was used to analyze complete data. Results: The mean of the patients was 52.4 ±12.37 years and had mean BMI 27.2±8.51 kg/m2. Majority of the patients 63 (61.2%) were males and remaining 40 (38.8%) were females. There were 55 (53.4%) patients had hypertension and 32 (31.1%) cases had diabetes. Most common symptoms were fever, cough dyspnea among all cases. This study found a strong association between severe COVID-19 and an increased AST > 2ULN, GGT > 2ULN, lower albumin (p = 0.020), higher SIRS (p = 0.045), higher procalcitonin, higher ferritin, lower pO2 (p = 0.044), and an elevated SOFA (p = 0.002), which is indicative of an inflammation response. A greater rate of COVID-19-related mortality was found to be associated with elevated levels of direct bilirubin, low albumin, tachypnea, and leukocytosis, according to the study's findings. Conclusion: We found that individuals with COVID-19 have indications of liver damage, which we believe is due to an inflammatory response that corresponds with the severity of COVID-19.